Fullerene movement in a carbon nanocontainer - Bubenchikov, Alexey M.; Bubenchikov, Mikhail A.; Chelnokova, Anna Sergeevna; Mamontov, Dmitriy V.; Lun-Fu, Aleksandr V. (Crystals)
The character of C-60 fullerene motion inside a cylindrical carbon nanocontainer with flat graphene covers has been studied. A new trajectory approach to describe the three-dimensional motion of fullerene is presented, based on the use of motion equations for its center of mass in the field of van der Waals forces, as well as the rotational motion equations written in the absolute basis. A high-precision computational technology for implementing this approach is described. Calculations have shown the components of the C-60 angular velocity change stepwise. This character of the change in rotation is determined by the impacts of the fullerene on the wall of the container. As a result of these impacts, the energy of rotation changes abruptly.